Steroid-resistant nephrotic syndrome: past and current perspectives - Nourbakhsh N; Mak RH (Dove Medical Press, 2017)
Noureddin Nourbakhsh, Robert H Mak Division of Pediatric Nephrology, Rady Children’s Hospital San Diego, University of California, San Diego, La Jolla, CA, USA Abstract: Patients with steroid-resistant nephrotic syndrome (SRNS) represent a challenging subset of patients with nephrotic syndrome who often fail standard immunosuppression and have a higher likelihood of progressing to end-stage renal disease. Appropriate treatment of SRNS requires an adequate understanding of the historical treatment, renal histopathology, and genetics associated with the disease. The aim of this review is to present a comprehensive appraisal of the history, role of renal biopsy, genetics, and treatment of SRNS. Keywords: steroid-resistant nephrotic syndrome, focal segmental glomerulosclerosis